Prognostic impact of lymph node parameters in distal cholangiocarcinoma after pancreaticoduodenectomy - Lyu, Shaocheng (World J Surg Oncol, 2020)
BACKGROUND: Pancreaticoduodenectomy is the only definitively curative therapy for the long-term survival of distal cholangiocarcinoma patients. Lymph node metastasis is widely accepted as an important prognostic factor for distal cholangiocarcinoma. The latest American Joint Committee on Cancer (AJCC) TNM classification system for distal cholangiocarcinoma has divided the lymph node metastasis patients into N1 and N2 by lymph node metastasis number. However, some studies suggested that the lymph node metastasis ratio may be better than the lymph node metastasis number. Therefore, we develop a program to analyze the correlation between lymph node parameters (lymph node dissection number, lymph node metastasis number, and lymph node metastasis rate) and long-term prognosis. METHODS: We retrospectively reviewed 123 distal cholangiocarcinoma patients after pancreatoduodenectomy from January 2011 to December 2019. The patients were grouped according to lymph node metastases and tumor-free and overall survival rates which were investigated with the Kaplan-Meier analysis. The logistic regression models were used for multivariate analysis to determine the risk factors for lymph node metastases. And the X-tile program was used to calculate the cutoff values for the lymph node parameters that discriminated survival. RESULTS: The 1-year, 3-year, and 5-year overall survival rates of patients with distal cholangiocarcinoma after pancreatoduodenectomy were 75.2%, 37.1%, and 31.5%, respectively. And the 1-year, 3-year, and 5-year overall survival rates of patients without and with lymph node metastasis were 83.0%, 50.7%, and 42.5% and 63.5%, 19.0%, and 19.0% (p = 0.000), respectively. Logistic regression showed CA19-9 and portal vein system invasion as independent risk factors for lymph node metastases. The receiver operating characteristic curve showed the optimal cutoff value of CA19-9 to predict the lymph node metastases was 75.5 U/mL. Determined by the X-tile software, the optimal cutoff values of the lymph node dissection number were 24 (p = 0.021), the lymph node metastasis number were 1 and 7 (p = 0.504), and the lymph node metastasis rate were 0.13 (p = 0.002). CONCLUSION: Lymph node metastasis is an important factor affecting the long-term survival of distal cholangiocarcinoma patients.CA19-9 and portal vein system invasion are independent risk factors for lymph node metastasis. Besides, the lymph node dissection number and lymph node metastasis rate can predict the long-term survival better than lymph node metastasis number.